The Influence of Problem Based Learning on Critical Thinking Skill Reviewed From Gender - Dewi, Sari; Ratnawati , Nurul; Dora , Nuriza; Mohd Hairy Ibrahim (Universitas Negeri Surabaya, 2024)
This research highlights the need for the application of learning models that can improve critical thinking skills. The model that is believed to be able to improve critical thinking skills is Problem Based Learning (PBL). The purpose of this study was to determine 1) the effect of PBL learning model on critical thinking ability; 2) the effect of gender differences on critical thinking ability; 3) the effect of PBL learning model on critical thinking ability in terms of gender differences. The purpose of this study was to determine the difference and effect of problem-based learning and discovery learning models on critical thinking ability in terms of gender. This research used quantitative approach with quasi experiment design. This research instrument used an essay test of 5 questions. The data analysis used was normality test, homogeneity test, and 2-way anova test. The results showed that 1) PBL model has an effect on students‘ critical thinking skills; 2) there is an effect of gender on students’ thinking skills; 3) there is no effect of PBL learning model on critical thinking skills in terms of gender differences.